2019
DOI: 10.1039/c8nr07521b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube functionalization as a route to enhancing the electrical and mechanical properties of Cu–CNT composites

Abstract: Density functional theory calculations supported by sonication experiments show that nitrogen doping of CNTs can effectively improve adhesion between them and the Cu matrix, and hence the mechanical properties and most importantly the electrical performance of the composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…Specially, for CNT–Cu contacts, Li et al found that a composite conductor using pure metallic CNTs, as opposed to a metallic–semiconducting mix of CNTs, will only slightly improve conductor performance. Recently, Milowska et al reported that a CNT–M–CNT (M = Ni, Cr) bimetal systems exhibit a reduced contact resistance owing to the increase in the density of interface states, and that nitrogen doping of CNT can effectively enhance both the mechanical and electron transport properties for CNT–Cu composites. Very interestingly, Hafizi et al recently predicted that the CNT–Cu contact can induce the collapse of larger‐diameter CNT, increase metal‐induced doping of the CNT, and thus reduce the resistance by increasing the number of conduction channels (however, such enhancement can be partially compensated by an additional scattering at the contact).…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 99%
“…Specially, for CNT–Cu contacts, Li et al found that a composite conductor using pure metallic CNTs, as opposed to a metallic–semiconducting mix of CNTs, will only slightly improve conductor performance. Recently, Milowska et al reported that a CNT–M–CNT (M = Ni, Cr) bimetal systems exhibit a reduced contact resistance owing to the increase in the density of interface states, and that nitrogen doping of CNT can effectively enhance both the mechanical and electron transport properties for CNT–Cu composites. Very interestingly, Hafizi et al recently predicted that the CNT–Cu contact can induce the collapse of larger‐diameter CNT, increase metal‐induced doping of the CNT, and thus reduce the resistance by increasing the number of conduction channels (however, such enhancement can be partially compensated by an additional scattering at the contact).…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 99%
“…75 It should be noted that in vicinity of defects, metals can form localized σ bonds or covalent bonds similar to end-contacts which have higher bonding energy. 28,66,76 A simple defect, such as a vacant carbon atom can drastically alter the nature of CNT-metal bonding.…”
Section: Interfacementioning
confidence: 99%
“…Recently, modifying the surface of CNTs through nitrogen doping and cysteamine grafting have shown promising results for fabrication of highly conductive Cu-CNT structures. 28,76 Chemical surface modification techniques and their applications will be discussed in details in the following sections.…”
Section: Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…), which have no durability and are quite inappropriate to the pure carbon assemblies. The topic has not received so far all the attention it deserves and very few studies have been targeted at this issue (Burda et al, 2015;Ebrahimian and Kokabi, 2017;Kim et al, 2018;Milowska et al, 2019;Fu et al, 2020).…”
Section: Frontiers Of the Current Technologymentioning
confidence: 99%